Aplikasi Instrumen Analisis Kebutuhan Berbasis Potensi Masalah Siswa - Akhmad Rizkhi Ridhani; Jarkawi Jarkawi (Bulletin of Counseling and Psychotherapy, 2022)
Guidance and counseling as a systematic, objective, logical, and sustainable and programmed effort carried out by counselors or Guidance and Counseling teachers to facilitate the development of students/counselors to achieve independence in their lives, of course, must also utilize this Technology and Information to be more effective and efficient in carrying out therapeutic services (helping relationships). What is unavoidable today is related to advances in technology and information. The purpose of this study is to design a needs analysis instrument application based on the potential problems of students in high school in the city of Banjarmasin. The method used is research and development (R&D) which focuses on designing a needs analysis instrument application based on the potential problems of students in senior high schools in Banjarmasin. The result of this research is that the model developed by the researcher is based on primary and secondary data. The conclusion of this study is that the model that has been developed can be continued to the validation stage of experts and practitioners to obtain its advantages and disadvantages so that it can be followed up to the trial stage and disseminated to users in high school formal education institutions.